Super Encryption of Rabin Cryptosystem Algorithm and Paillier Cryptosystem Algorithm on Digital Image Security Process - Ramanda, Dika; Achmad Fauzi; Pakpahan, Victor Maruli (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Technological advances have given rise to the need for data protection, especially digital images, which are vulnerable to misuse. This research proposes a super encryption method that combines two cryptographic algorithms, namely Rabin Cryptosystem and Paillier Cryptosystem, to increase digital image security. Rabin's algorithm does not have homomorphism, so it is vulnerable to factorization attacks if the prime numbers used are too small. Meanwhile, the Paillier algorithm has homomorphism properties which allow arithmetic operations to be carried out directly on the ciphertext without decryption. By combining these two algorithms, this research aims to create a stronger and more efficient encryption method, and analyze its performance in terms of computational efficiency and complexity. It is hoped that the research results can improve the security and privacy of digital data, especially in the context of digital images.